Pembelajaran Integratif Manajemen Pesantren Berbasis Kurikulum Merdeka - Amaliyah, Amaliyah; Darmawan, Deni; Merdeka, Muhamad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Demands for changes in the learning process from the educational aspect, as a manifestation of developments in science and technology. Students must be accustomed to thinking critically, constructively, thinking systematically, complexly and in stages. Students' abilities must be trained by providing opportunities to explore their abilities so that they can discover knowledge concepts resulting from learning activities. Of course, these demands must be in synergy with the teacher's competence in managing the class and implementing integrative learning methods in the process. This is in accordance with the independent curriculum policy in higher education. This research uses integrative learning with several methods, starting with the pre-cycle with the expectory learning (lecture) method, cycle 1 with the problem based learning method and cycle 2 with the project based learning method. The results of classroom action research using integrative learning in Islamic boarding school management courses can increase student abilities. That integrative learning can encourage student learning activities.